Neural Engineering - He, Bin.; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2013)
Neural Engineering, 2nd Edition, contains reviews and discussions of contemporary and relevant topics by leading investigators in the field. It is intended to serve as a textbook at the graduate and advanced undergraduate level in a bioengineering curriculum. This principles and applications approach to neural engineering is essential reading for all academics, biomedical engineers, neuroscientists, neurophysiologists, and industry professionals wishing to take advantage of the latest and greatest in this emerging field.
Keywords: Engineering; Neurosciences; Radiology, Medical; Biomedical engineering; Engineering; Biomedical Engineering; Neurosciences; Biophysics and Biological Physics; Imaging / Radiology